OCHRONA WOLNOŚCI I PRAW EKONOMICZNYCH A GRANICE OPODATKOWANIA - ZASADY I KONTROWERSJE - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 2005)
The content of tax rules, and, consequently, the whole taxation system is never free from a political aspect. Taxes have always been, and shall remain, an issue related to power. Therefore the decisions how the tax burden shall be distributed, even if taken by parliament, will never be free from political pressures. Consequently, it is even more important to secure transparency of the tax rules, especially of those which impose tax obligations, because those are too often blurred and contain a vested interest of a certain pressure group which has helped a given politician to raise to power, or has at least contributed to his attaining of political power. Politicians should remember that the way to understand taxes leads through the understanding of the essence of a state. Therefore, in the course of tax legislation, care should be taken to ensure that the common good prevails and wins over a particular interest, and that conflicts of interests and political disputes are given in, to allow real cooperation in the legislative work on taxes. Only such a situation will allow creation of constitutionally legal relations between the state and a tax payer. Further, it must be remembered that even if a politician is tempted to interfere with the tax law and violates constitutional standards for a period of time, lawlessness never creates law. And then, we may reflect whether indeed fiscus non erubescit.
PROTECTION OF FREEDOM OF ECONOMIC ACTIVITY AND ECONOMIC RIGHTS VS TAXATION - PRINCIPLES AND CONTROVERSIES